Halal SMEs: young entrepreneur’s involvement - Abdul Rahman , Rozailin (2015)
In congruence with the acceptance of Halal business throughout the world, entrepreneurs in Malaysia also use new and innovative strategies to compete with other business in the global market. This is due to the Halal products that provide assurance and commitment to the consumer that the products or service is safe to be consumed or used. However, there are not many SMEs equipped with trusted Halal certification. Plus, the involvement of the young entrepreneur in Halal market is very small. They have the products, but without any Halal certification, their products cannot go far. The paper intends to explore the perception and attitude of the Malaysia young entrepreneurs towards the acceptance of Malaysia JAKIM Halal certification and their involvement in Halal SMEs. 120 randomly selected young entrepreneurs based in rural and urban area have been interviewed. The results shows that male entrepreneurs are more willing to accept Malaysia JAKIM Halal certification compared than female and those with higher level of education prefer to obtain the certificates compared those with lower level of education. Out of 120 respondents, 49 of them were involved directly with Halal products and services and only 17 have their products certified with Malaysia JAKIM Halal certification.